Progression of experimental chronic peri-implantitis in dogs: Clinical and radiographic evaluation - Martins, M. C.; Shibli, J. A.; Abi-Rached, RSG; Marcantonio, E. (Amer Acad Periodontology, 2005)
Background: the aim of this study was to evaluate the progression of experimental peri-implantitis in dogs using implants with different surface coatings.Methods: Thirty-six dental implants with four different surface coatings, commercially pure titanium (cpTi), titanium plasma-sprayed (TPS), hydroxyapatite (HA), and acid-etched (AE), were placed in six mongrel dogs. Five months after implantation, peri-implantitis was induced by cotton ligatures to facilitate plaque accumulation for 60 days. After 60 days, the ligatures were removed and supragingival plaque control was initiated for 12 months. Probing depth (PD), clinical attachment level (CAL), vertical bone level (VBL), horizontal bone level (HBL), and mobility were obtained at baseline, and 20, 40, 60 (acute phase), and 425 days (chronic phase) after ligature removal.Results: PD and CAL changed around all implant surfaces after ligature placement (P < 0.0001). However, the means of PD and CAL were not statistically significant among the different surfaces (P > 0.05). The range of CAL variation, calculated between baseline and 60 days (acute phase) and between 60 and 425 days (chronic phase), decreased (P < 0.05). Bone loss increased during the entire experiment (P < 0.0001). The HA surface showed the greatest bone loss measurement (5.06 +/- 0.38 mm) and the TPS showed the smallest bone loss (4.27 +/- 0.62 mm). However, statistical significance was not assessed for different coatings (P > 0.05).Conclusions: the clinical data at the initial phase showed rapid and severe peri-implant tissue breakdown. However, removal of ligatures did not convert the acute destructive peri-implant phase to a non-aggressive lesion and the progression of peri-implantitis was observed at chronic phase. The,experimental peri-implantitis in dogs may be a useful model to evaluate the progression of peri-implantitis.
Keywords: animal studies; dental implants/adverse effects; dental implants/complications; follow-up studies; peri-implant diseases/prevention and control